The role of creative ability in enhancing the mental image of insurance companies : applied research (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The aim of the research is to explore the possibility of enhancing the mental image through its dimensions (perception, influence, motivation, and desire) via creativity to face the challenges that insurance companies encounter, which are responsible for providing services to a large segment of society. The main issue of the study is the low and weak insurance culture among the public, the lack of a good mental image of insurance companies, especially in Iraq, and the low demand for purchasing insurance services, The study used the financial reports of the Iraqi Insurance Company, in addition to conducting personal interviews with the officials. The research was applied to the Iraqi Insurance Company, and the researcher concluded several findings, most notably the lack of special attention by the company's management to investments and the absence of an appropriate policy for investment allocation and ensuring their safety. However, the company's management is progressing with an investment development policy, which shows the company's ability to meet its obligations to the insured, positively reflecting on the company's profitability.